STRATEGI DAN KEGIATAN HUMAS DALAM MENINGKATKAN CITRA MADRASAH - Alamsyahbani Alamsyahbani; Tedy Christiyanto; Riza Febri Masriyani; Fridila Zasyiva; Husni Fadilah (STKIP Pesisir Selatan, 2026)
This study aims to describe the public relations strategies and activities implemented at MAN 2 Kota Jambi in building a positive and professional image of the educational institution. The approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation of public relations activities. The research findings indicate that the role of public relations is not limited to publishing and documenting school activities but also includes a strategic role in bridging communication between the school and the public, particularly parents and the community. The public communication strategies implemented include the use of digital platforms such as websites, Instagram, Facebook, YouTube, TikTok, and plans to launch a podcast. Additionally, public relations applies strict information selection principles before publication to maintain the institution's credibility and image. The digital innovations developed demonstrate the adaptability of public relations in addressing communication challenges in the information technology era. This study emphasizes that effective and responsive public relations is a key factor in building the reputation of an inclusive and trustworthy educational institution.